Effect of blending plastic pyrolytic oil and waste cooking biodiesel on engine performance, emissions and lubricity of a small diesel engine fuel with palm oil biodiesel (B30) / Muhamad Sharul Nizam Awang - Muhamad Sharul Nizam, Awang (2021)
Malaysia is expected to adopt B30 (30% palm oil biodiesel (POB) content in diesel) by 2025. However, because 30% POB degrades diesel engine performance and increases exhaust emission, it is not advised for use in diesel engines. Plastic waste and waste cooking oil are preferable alternatives to be converted into fuel and blended with POB and diesel to generate B30 blends due to their cost-effectiveness and abundant availability in Malaysia, provided that these wastes are appropriately handled. The objectives of this study were to study the diesel engine performance and emission characteristics of quaternary fuels, comprising waste plastic pyrolytic oil (WPPO), waste cooking oil biodiesel (WCOB), POB and diesel as well as to analyse their lubricity properties. Gas chromatography-mass spectrometry (GC-MS) was used to examine their compositions. Mechanical stirring was used to prepare four quaternary fuels with varying compositions. B30a (30% POB and 70% diesel) mixture was prepared as a reference fuel. To enhance fuel characteristics, engine performance, and emission parameters, 5%, 10%, and 15% of each WPPO and WCOB were blended with POB-diesel blend. The POB of the quaternary fuel mixture was kept constant at 10%. The findings were compared to Malaysian commercial diesel (B10) and B30a fuel. All quaternary fuel blends' brake power (BP) and brake thermal efficiency (BTE) were enhanced by up to 2.78 % and 9.81 %, respectively, when compared to B30a fuel. All quaternary fuels exhibited a reduction in brake-specific fuel consumption (BSFC) when compared to B30a. B40 quaternary fuel showed the maximum reduction in carbon monoxide (CO) and carbon dioxide (CO2) emissions by 19.66 and 4.16%, respectively when compared with B30a. When compared to B30a, the B20 quaternary mix demonstrated a maximum reduction of 41.86 % in hydrocarbon (HC) emissions. The average coefficient of friction (COF) of the quaternary fuel mixtures B40, B30b, and B20 were lowered by 7.63, 6.89, and 3.17%, respectively, when compared to B10. As a conclusion, quaternary blends have a high potential to be used in diesel engine.